2021
DOI: 10.33140/jcei.06.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Effects of Imuno TF® (transfer factors) on Th1/Th2/Th17/Treg Cytokines

Abstract: Transfer factors are known since 1955 due to their activities on the immune system. Although the reports on the effects on diverse immune mechanisms, their role on Th1, Th2, Th17 and Treg responses was still not described. In this sense, the present work focused on the evaluation of such immune responses. For that, human lymphocytes, and mice thymic, splenic and Peyer’s cells were stimulated with Lipopolysaccharides and Concanavalin A, and then treated with isolated transfer factors (Imuno TF®). The culture me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although immunological transfer factors are still controversial due to the lack of studies that can adequately address their characterization and functionality, our group has investigated such molecules from a specific food supplement to standardize the findings. In fact, our group has shown that oral feeding of Imuno TF ® is efficient and safe ( 17 ). Subsequently, our group demonstrated that Imuno TF ® upregulated Th1 cytokines and downregulated Th2 cytokines, once Imuno TF ® decreased secretion of IL-4, IL-5, IL-6, IL-13 and TNF, and conversely Imuno TF ® increased secretion of anti-inflammatory IL-10 ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although immunological transfer factors are still controversial due to the lack of studies that can adequately address their characterization and functionality, our group has investigated such molecules from a specific food supplement to standardize the findings. In fact, our group has shown that oral feeding of Imuno TF ® is efficient and safe ( 17 ). Subsequently, our group demonstrated that Imuno TF ® upregulated Th1 cytokines and downregulated Th2 cytokines, once Imuno TF ® decreased secretion of IL-4, IL-5, IL-6, IL-13 and TNF, and conversely Imuno TF ® increased secretion of anti-inflammatory IL-10 ( 18 ).…”
Section: Introductionmentioning
confidence: 99%